The new Spanish immigration law and breach of Rupture Tampere? ¿Innovation or follow the Italian model? - Álvarez Rodríguez, Aurelia Álvarez Rodríguez (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Starting from the political and legal context in Spain, an analysis is made of the new Organic Law 4/2000. It does not seek so much to account for this law and for its difficult birth, but rather to place it within the framework of the European Union as its future contextsof application. In order to do this, after a brief reflection on the present regulations of the EU, the new law is compared with the present italian legislation on foreigners and on immigration.